2004
DOI: 10.1002/art.20561
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of erythrocyte C4d and complement receptor 1 in systemic lupus erythematosus

Abstract: Objective. C4-derived activation fragments are the only complement ligands present on the surfaces of normal erythrocytes. The significance of this observation is unknown, and the role of erythrocyte-bound C4 (E-C4) in human disease has not been explored. More than any other human disease, the pathogenesis of systemic lupus erythematosus (SLE) has been characterized by defects in clearance of complement-bearing immune complexes via erythrocytes expressing complement receptor 1 (CR1). This study was undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
93
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 19 publications
6
93
0
Order By: Relevance
“…Previous studies conducted by us (15) and by other investigators (16,17) have shown the presence of C4d, a complement activation product, on the surface of erythrocytes. To evaluate the potential of reticulocyte C4d levels as a biomarker of disease activity, we conducted a cross-sectional study to examine and compare the presence of C4d on reticulocytes from healthy subjects, patients with SLE, and patients with …”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Previous studies conducted by us (15) and by other investigators (16,17) have shown the presence of C4d, a complement activation product, on the surface of erythrocytes. To evaluate the potential of reticulocyte C4d levels as a biomarker of disease activity, we conducted a cross-sectional study to examine and compare the presence of C4d on reticulocytes from healthy subjects, patients with SLE, and patients with …”
Section: Resultsmentioning
confidence: 85%
“…We recently demonstrated that erythrocytes in patients with SLE are characterized specifically by abnormally high levels of erythrocyte C4d and abnormally low levels of erythrocyte CR1 (15). The capacity of C4-derived complement activation products to attach covalently to cell surfaces via thioester bonds suggests that erythrocytes, once tagged with C4d, may carry the molecule during the remainder of their lifespan (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently identified abnormal levels of the complement-activation product C4d on erythrocytes from patients with SLE (10). Erythrocyte C4d appears to be a useful lupus biomarker for diagnosis and monitoring of disease activity over time.…”
mentioning
confidence: 99%